Sulfated hyaluronic acid inhibits the hyaluronidase CEMIP and regulates the HA metabolism, proliferation and differentiation of fibroblasts - Schmaus, Anja; Rothley, Melanie; Schreiber, Caroline; Möller, Stephanie; Roßwag, Sven; Franz, Sandra; Garvalov, Boyan K.; Thiele, Wilko; Spataro, Sofia; Herskind, Carsten; Prunotto, Marco; Anderegg, Ulf; et al. (Matrix biology, 2022)
Hyaluronan (HA) is an extracellular matrix component that regulates a variety of physiological and pathological processes. The function of HA depends both on its overall amount and on its size, properties that are controlled by HA synthesizing and degrading enzymes. The lack of inhibitors that can specifically block individual HA degrading enzymes has hampered attempts to understand the contribution of individual hyaluronidases to different physiological and pathological processes. CEMIP is a recently discovered hyaluronidase that cleaves HA through mechanisms and under conditions that are distinct from those of other hyaluronidases such as HYAL1 or HYAL2. The role of its hyaluronidase activity in physiology and disease is poorly understood. Here, we characterized a series of sulfated HA derivatives (sHA) with different sizes and degrees of sulfation for their ability to inhibit specific hyaluronidases. We found that highly sulfated sHA derivatives potently inhibited CEMIP hyaluronidase activity. One of these compounds, designated here as sHA3.7, was characterized further and shown to inhibit CEMIP with considerable selectivity over other hyaluronidases. Inhibition of CEMIP with sHA3.7 in fibroblasts, which are the main producers of HA in the interstitial matrix, increased the cellular levels of total and high molecular weight HA, while decreasing the fraction of low molecular weight HA fragments. Genetic deletion of CEMIP in mouse embryonic fibroblasts (MEFs) produced analogous results and confirmed that the effects of sHA3.7 on HA levels were mediated by CEMIP inhibition. Importantly, both CEMIP deletion and its inhibition by sHA3.7 suppressed fibroblast proliferation, while promoting differentiation into myofibroblasts, as reflected in a lack of CEMIP in myofibroblasts within skin wounds in experimental mice. By contrast, adipogenic and osteogenic differentiation were attenuated upon CEMIP loss or inhibition. Our results demonstrate the importance of CEMIP for the HA metabolism, proliferation and differentiation of fibroblasts, and suggest that inhibition of CEMIP with sulfated HA derivatives such as sHA3.7 has potential utility in pathological conditions that are dependent on CEMIP function.